KAPABILITAS KOMISI PEMILIHAN UMUM DAERAH (KPUD) KOTA PEKANBARU PADA PEMILU SERENTAK TAHUN 2019 - Vega Putra; Erman M (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
General Election is an activity for all people to participate in choosing someone who is worthy to be a leader in an area that he occupies. The simultaneous election is present as a consequence of the Constitutional Court Decision 14 / PUU-XI / 2013 which changed the timing of the presidential and legislative elections which were initially separated to be held at the same time. The Concurrent Election is considered to be able to make election administration more efficient and save the state budget. In fact, the implementation of the 2019 Concurrent Election is still faced with problems. The General Election Commission (KPU) as the organizer and organizer of the election has an important role in the success of the General Election. This study aims to determine how the capability of the Regional General Election Commission (KPUD) of Pekanbaru City in holding the 2019 simultaneous general election. The theory used in this research is the Public Organization Capability Model according to Kusumasari, which has 4 variables, consisting of institutional capabilities, human resource (HR) capabilities, financial or budget capabilities, and technical implementation capabilities. The location of this research was conducted in Pekanbaru City, especially in the Regional General Election Commission (KPUD) of Pekanbaru City.This research use desciptive qualitative approach. The data collection technique is done by interview and documentation. The results of this study are that the Regional General Election Commission (KPUD) is not yet capable of holding the 2019 simultaneous general election. This is caused by several factors such as a lack of institutional capability, financial capability, human resource capability and technical capability. Keywords: institutional capability, human resource capability (HR), financial capability, technical capability.